Keterampilan Berpikir Kritis Buku Ensiklopedia Famili Malvaceae Melalui Penelitian Pengembangan - Sari, Aprilila Kartika; Kaspul, Kaspul; Zaini, Muhammad (Yayasan Jompa Research and Development, 2024)
The 21st century is called the information century for all aspects of life. One of the abilities that 21st century education must have is critical thinking. Statistics on critical thinking abilities of biology students show that these abilities are still lacking. The use of teaching materials is one method for training critical thinking skills. The Encyclopedia Book is an instructional resource created during this project. To improve the quality of a product developed in the form of an encyclopedia, development research is needed. Seven types of plants from the Malvaceae family which are often found in the Banua Botanical Gardens are included in the encyclopedia created. The EDR (Educational Design Research) research method was applied in the study of making this encyclopedia. In terms of developing students' critical thinking skills, the results of the expected effectiveness test are in the good category with a total average score of 76.3%, while actual effectiveness is in the very good category with a total average score of 87.13%. This is suitable for use as a teaching tool both in theory and practice.